A study on industrial communication networking: ethernet based implementation - Hashim, Hairulazwan (2006)
Recent enhancement of the industrial communication and networking has made it possible to apply Ethernet networks at all levels of industrial automation, especially at controller level where the data exchange in real-time communication is mandatory. This report presents a study on the development of industrial communication network based on the Ethernet and thus implementation towards Computer Integrated Manufacturing (CIM) system. The Ethernet module is installed onto supervisory OMRON PLC to integrate the various stations in the CIM-70A system which located at Robotic Laboratory in KUiTTHO. The workability of this communication technique was analyzed and compared with the conventional serial communication which widely used in automation networking systems. Through this approach, the communication and integration of CIM systems can be accessed easily and hence available to be upgraded to the management and enterprise levels of automation.